2023
DOI: 10.3390/ph16030458
|View full text |Cite
|
Sign up to set email alerts
|

The Negative Impact of Triptolide on the Immune Function of Human Natural Killer Cells

Abstract: Triptolide (TP), a bioactive compound extracted the from traditional Chinese medicine Tripterygium wilfordii Hook F (TwHF), has been shown to be effective in treating several autoimmune diseases, and has suppressive effects in several key immune cells such as dendritic cells, T cells, and macrophages. However, it is unknown whether TP has an impact on natural killer (NK) cells. Here, we report that TP has suppressive effects on human NK cell activity and effector functions. The suppressive effects were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Previous studies have indicated that TP can modulate the functions of several immune cells such as natural killer cells and T‐helper 17 cells (Th17) cells, while suppressing the production of proinflammatory cytokines and chemokines. 17 , 18 Additionally, TP also suppresses cell proliferation and inflammation in fibroblast‐like synoviocytes (FLS). 19 , 20 These findings suggest that TP exerts a multi‐target regulatory function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that TP can modulate the functions of several immune cells such as natural killer cells and T‐helper 17 cells (Th17) cells, while suppressing the production of proinflammatory cytokines and chemokines. 17 , 18 Additionally, TP also suppresses cell proliferation and inflammation in fibroblast‐like synoviocytes (FLS). 19 , 20 These findings suggest that TP exerts a multi‐target regulatory function.…”
Section: Discussionmentioning
confidence: 99%